2008
DOI: 10.1097/hjh.0b013e3282ffdc66
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of retinal arteriolar structure in never-treated patients with essential hypertension

Abstract: The changes in arteriolar structure of retinal vessels in our study cohort revealed a similar pattern to that observed previously by other investigators in subcutaneous small arteries in essential hypertension. Blood pressure emerged as an important and independent determinant of wall-to-lumen ratio of retinal arterioles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
87
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 34 publications
7
87
0
2
Order By: Relevance
“…13 Indeed, by using SLDF, we could show that WLR of retinal arterioles is increased in patients with hypertension and cerebrovascular events compared with treated hypertensives and normotensives. 17 Moreover, we have shown that WLR seems to be a robust indicator of the severity of hypertension, 26 the presence of early renal damage, 27 and, in contrast with arteriolar-to-venular ratio, is related to the extent of atherosclerotic damage in the carotid artery, as indicated by evaluation of the intima-media thickness. 28 Hence, the major and novel finding of this observational study is that central PP is a strong and an independent predictor of vascular remodeling (WLR) in the retinal circulation beyond classical CV risk factors and additional factors that are proposed to have an impact on vascular structure.…”
Section: Discussionmentioning
confidence: 99%
“…13 Indeed, by using SLDF, we could show that WLR of retinal arterioles is increased in patients with hypertension and cerebrovascular events compared with treated hypertensives and normotensives. 17 Moreover, we have shown that WLR seems to be a robust indicator of the severity of hypertension, 26 the presence of early renal damage, 27 and, in contrast with arteriolar-to-venular ratio, is related to the extent of atherosclerotic damage in the carotid artery, as indicated by evaluation of the intima-media thickness. 28 Hence, the major and novel finding of this observational study is that central PP is a strong and an independent predictor of vascular remodeling (WLR) in the retinal circulation beyond classical CV risk factors and additional factors that are proposed to have an impact on vascular structure.…”
Section: Discussionmentioning
confidence: 99%
“…36 Mechanisms underlying the association of BP and retinal arterioles have been previously hypothesized. 3,38,39 Arteriolar narrowing is thought to result from cumulative arteriolar changes associated with remodeling from chronic hypertension and arteriolosclerosis. 3,38 Our findings showed that retinal arteriolar narrowing remained evident even in individuals whose BP had been lowered by antihypertensive therapy, suggesting persistent arteriolar damage from chronic hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…99 Using such approach, an increased wall:lumen ratio of retinal arterioles was initially demonstrated in treated hypertensive patients with cerebrovascular event, 100 as well as in untreated hypertensive patients. 101 Further recent studies report that increased wall:lumen ratio of retinal arterioles is correlated with increased BP, urinary albumin excretion, and cerebrovascular damage. [100][101][102][103] Compared with assessment of retinal arteriolar narrowing with retinal fundus photography, assessing wall:lumen ratio of retinal arterioles may provide further indication on vascular remodeling, but its prognostic significance has not yet been evaluated in prospective studies, and the technical availability of scanning laser Doppler flowmetry is limited.…”
Section: Assessment Of Retinal Vascular Flowmentioning
confidence: 99%